Prediction of Financial Distress and the Impact of the Covid-19 Pandemic on PT Garuda Indonesia for the period 2016-2021 - Budianto, Budianto; Falikhatun, Falikhatun (Jurnal Wacana Ekonomi, 2024)
This study aims to analyse the potential financial distress of PT Garuda Indonesia. This research uses the modified Altman Z-Score model approach. This study used quantitative descriptive methods with a case study approach at PT Garuda Indonesia. Measurement of financial health level is done using the Altman ratio model. The data source uses secondary data obtained directly from the company's website. This study used annual report data from 2016 to 2021. Based on the analysis of financial ratios, during the 2016-2021 period, the financial performance of PT Garuda Indonesia continued to decline. The results of the Altman-Z score calculation show that PT Garuda Indonesia is experiencing financial distress. This result is an early warning for PT Garuda Indonesia to improve its financial performance. Suggestions to the Government of Indonesia, through the Ministry of SOEs as the main shareholder in order to give full attention and support to PT Garuda Indonesia to avoid future bankruptcy risks.